Administration of Binahong (Anredera Cordifolia (Ten) Steenis) Leaves Extract Fixes Pancreatic β-cell Damage through Lowering Blood Glucose and Advanced Glycation End Products (AGEs) Level in Hyperglycemic Wistar Rat - Sri Wahyuni; I Wayan Putu Sutirta Yasa (Journal of Global Pharma Technology, 2017)
Background: Increasing production of free radicals is one of the factors that cause hyperglycemia. Chronic hyperglycemia can increase the production of reactive oxygen species (ROS), resulting in oxidative stress. The aim of this study is to determine the effectiveness of binahong (Anredera cordifolia (ten) steenis) leaf extract in fixing the pancreas β-cell damage rate in alloxan induced hyperglycemic Wistar rat. Methods: This study used randomized pre and post-test control group design. Fifty Wistar rats were divided into two control groups and three experimental groups administered with difference doses of binahong leaves extract; 0.5 mg/kg BW (P1), 2.0 mg/kg BW (P2), and 5.0 mg/kg BW (P3). Hyperglycemic state obtained by inducing the rats with alloxan. Results: The result showed that mean blood glucose levels were decreased in the positive control group (glibenclamide) (185.98 mg/dL) and the experimental groups; P1, P2, and P3 (181.36 mg/dL, 184.61 mg/dL, and 163.36 mg/dL, respectively). The mean differences between P1 and P2 and between P1 and P3 were statistically significant (p < 0.05). The AGEs level for the positive control group (glibenclamide) is 0.224 mol/L and for the experimental groups are 0.219 mol/L, 0.212 mol/L, and 0.188 mol/L for P1, P2, and P3, respectively. The differences were statistically significant. Conclusions: Administration of binahong leaves extract can improve the damage rate of pancreas β-cell through lowering the blood glucose and AGEs level in hyperglycemic Wistar rat and that the effect is significant at the dose of 5.00 mg/kg bw per day.Keywords: Anredera cordiofolia (ten) steenin, blood glucose and AGEs, hyperglycemia.